The problem of disenchantment scientific naturalism and esoteric discourse, 1900-1939 - Asprem, Egil 1984- (Studies in the history of religions, 2014)
8 Laboratories of Enchantment: Parapsychology in Search of a Paradigm9 Professionals Out of the Ordinary: How Parapsychology Became a University Discipline; Part 4 Esoteric Epistemologies; 10 Esoteric Epistemologies; 11 The Problems of a Gnostic Science: The Case of Theosophy's Occult Chemistry; 12 Perceiving Higher Worlds: Two Perspectives; Conclusion: Implications for the Study of Science, Religion, and Esotericism; Bibliography; Index of Names; Index of Subject.